ANALYSES OF COSTS AND RETURN OF DATE PALM FRUITS (Phoenix dactylifera Linn) MARKETING AMONG RETAILER TRADERS IN KADUNA METROPOLIS, KADUNA STATE, NIGERIA - Ariyo, Oluyinka Christopher (Agricultural Socio-Economics Journal, 2023)
Date palm trees are an economic crop which fruits are used for food, medicine and income in the arid and semi arid zone of Nigeria. The study was undertaken to analyse the costs and return of date palm fruits marketing among retailer traders in Kaduna metropolis, Kaduna. Two-stage sampling technique was employed which led to random selection of 80 respondents. Structure questionnaires were administered to the respondents and data collected were analysed with descriptive statistics, cost and return, and regression analysis. The results showed that all the respondents are male, 21-30 years of age, married with household size of 6-10 family members and had Qur’anic education. The result further showed that marketing of date fruits was profitable with net marketing income of N 8,400 per respondent per month and return on investment of N 0.11. Variables such as years of marketing experience, quantity of date palm purchased and revenue were significant at (P< 0.01) percent probability level. Also purchase cost and quantity of date palm sold were significant at (P< 0.05) percent while transportation cost and household size were significant at (P < 0.10) percent. The major constraints of date fruits marketing are inadequate capital, pest infestation, inadequate storage facilities and insecurity. The study recommends that unemployed teeming population especially youths should be encouraged to go into the business of date palm fruits marketing to earn a living.